Rural Farmer‐Managed Wetland Agroecosystems Promote Climate Resilience in Semi‐Arid Savannah: Case of Nyororo Wetland, Mberengwa District, Zimbabwe - Pascal Manyakaidze; Regis Musavengane; Robert Maponga (Climate Resilience and Sustainability)
ABSTRACT Climate change is threatening the resilience of smallholder agroecosystems in semi‐arid areas. Wetland agroecosystems provide critical life support and positive outcomes for people, nature and climate in semi‐arid areas. Wetland shrinkage, degradation, species extinction and habitat loss have threatened livelihoods and ecosystems across the globe. The study aimed to determine climate change impacts on farmer‐managed wetland agroecosystems and evaluate resilience‐building strategies in semi‐arid rainfall marginal areas, focusing on Nyororo wetland in Mberengwa district. A mixed method approach informed data collection and analysis, influenced by interpretivism and objectivism research philosophical underpinnings. The mixed methods approach enabled the study to benefit from multiple knowledge domains, including professional ecological knowledge (PEK), scientific ecological knowledge (SEK), bureaucratic ecological knowledge (BEK), technological ecological knowledge (TEK) and local ecological knowledge (LEK). Information gathered through semi‐structured questionnaires, interviews, focus group discussions, key informant interviews, secondary data, remote sensing and scientific measurements was synthesised to bring the resilience picture around wetland‐based agroecosystems. The study findings on wetland degradation and climate change impacts on wetland agrobiodiversity included wetland shrinkage, an increase in invasive floral species by 25%, declining groundwater, reduced dryland cereal (Zea mays) production by 77.16% over a 41‐year period, and the occurrence of crop pests and animal diseases, which had negative outcomes on wetland provisioning, regulatory services and ecosystem health. Resilience‐building strategies, including adopting seasonal livelihood programmes, ecosystems‐based adaptation (EbA) strategies such as wetland farming, protection of wetland water sources, harvesting wetland goods for selling and anticipatory action planning (AAP), including planting drought‐tolerant, short‐seasoned food crops, proved effective in the sustainable management of wetlands agroecosystems. The study recommended that financial mechanisms be tailored to suit the needs of local communities’ conservation and resilient livelihoods. The study recommends that stakeholders swiftly implement the promising wetland agroecosystem resilience‐building strategies that bring positive outcomes for people, nature and climate.